Odontometric parameters in human mandibular molars for sex estimation in a forensic context - Sofia Fernandes Franco; Álvaro Azevedo; Vítor M. J. Matos; Daniel Mongiovi; Alexandra Teixeira (Dental Anthropology Association, 2021)
When encountering human skeletal remains in forensic contexts, one important step in the identification process is the estimation of sex, because it reduces the number of individuals to approximately one half. The pelvis and skull are considered the most efficient elements for this estimation; however, when unavailable, teeth may be used alternatively. This study aims to evaluate the usefulness of specific odontometric parameters from the mandibular first molar - mesiolingual-distobuccal distance (MLDB) and mesiobuccal-distolingual distance (MBDL) - on sex estimation, in a sample composed from 135 mandibles selected from the Coimbra Identified Skeletal Collection (University of Coimbra). Since canines seem to be the most accurate teeth for sexual diagnosis, comparison of molars parameters and canines was performed, through measurement of their mesiodistal dimensions (MD). Statistical analysis showed sexual dimorphism in human first molars and determination of cut-off points assigned individuals to the male or female group. In the first molar, 60.7% and 65.2% of individuals were correctly classified by using MLDB and MBDL, respectively. Highest sexual diagnosis accuracy was achieved with Canine MD, reaching 74.6%. Our results indicate that although mandibular molar dimensions are useful for sex estimation, the canine should be prioritized when using the dentition to perform this task.